Respon Nahdatul Ulama Terhadap Gagasan Politik Islam Radikal di Indonesia - Hasbi Aswar (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2016)
The aim of this paper is to explain the role of Nahdlahtul Ulama in Indonesia in countering the arguments and propagandas of pro-Islamic State or radical  movements in Indonesia. Nahdlatul Ulama is one of most prominent islamic organizations in Indonesia which has million followers. It has very big role in the process of Indonesian politics since pre-independence era until now and  Nahdlatul Ulama has moderate thinking on the relation between Islam and state where NU acknowledge the concept of nationalism and democracy in Indonesia. The rise of pro-Islamic State Movements in Indonesia with  rejecting the concept of nationalism and democracy automatically become an important issue to Nahdlatul Ulama. In this paper, NU by its leaders, and its scholars shows its position either individually or institutionally to reject the idea that is brought by the pro-Islamic Khilafah State.